Devolution and welfare: the social and legal implications of state inequalities for welfare reform in the United States - Whitaker, Ingrid Phillips (Social justice, 2001)
Part of a special issue on welfare and punishment in the era of President George W. Bush. The writers analyze the 1996 Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA), its federalist characteristics, and the social and legal implications for welfare reform of inequalities between states. They argue that the federal government's relinquishment of most of its responsibility to the states for providing for poor families raises the question of whether federal funding for welfare programs in the U.S. is fundamentally discriminatory. They conclude that reformation of public assistance for poor families and children is needed, but that reform that creates further disparities between states is questionable, given the inequalities that already exist.